“Turn-Off” Fluorescent Sensor for Pamidronate Disodium and Zoledronic Acid Based on Newly Synthesized Carbon Dots from Black Tea - Peng Li; Yongcheng Hu (Journal of Analytical Methods in Chemistry)
As common bisphosphonates drugs, pamidronate disodium and zoledronic acid have been widely investigated for bone metastases. In this paper, a new “turn-off” model based on carbon dots (CDs) from black tea was established to analyze the two kinds of bisphosphonate drugs, pamidronate disodium and zoledronic acid. Through the new sensor, both of drugs can be quantitative, respectively, with the limit of detection of 5 × 10−9 mol·L−1 and 6 × 10−9 mol·L−1. In addition, the fluorescence of newly prepared CDs can be quenched by two drugs with various degrees via photoinduced electron transfer, which can be perfectly used to distinguish them. Most importantly, this turn-off method has been employed to analyze the two drugs under the influence of foreign interference factors. This method provides a new view and guidance for the rapid analysis and recognition of drugs for bone metastases in vitro and in vivo.